Repro-sexual intersections: sperm donation, HIV prevention and the public interest in semen. Issue 3 (March 2015) - Pralat, Robert
Abstract In the scientific literature on fertility and assisted reproduction, and in the corresponding area of clinical practice, increasing attention has been paid to two groups: people living with the human immunodeficiency virus (HIV) and gay men. However, research on fertility in the context of HIV focuses almost exclusively on heterosexual couples, whereas studies on non-heterosexual reproduction rarely mention HIV, despite the fact that, in many western countries, HIV prevalence among men who have sex with men is higher than ever before and men who have sex with men are the only group in which new HIV infections are on the rise. This review identifies links between reproduction, HIV and homosexuality, showing that, historically, they are closely intertwined, which has important implications for current issues facing HIV care and fertility services. Considering sex and parenthood as two different but related kinds of intimacy and kinship, the dual role semen plays in sexually transmitted infection and in assisted reproduction is discussed. The review reflects on the future of sperm donation and HIV prevention, asking whether two challenges that potentially face healthcare and medicine today – the shortage of 'high-quality' sperm and the 'surplus' of infected semen – could be addressed by a greater exchange of knowledge.